Prove that sin^4x - cos^4x = 2sin^2x - 1
1 answer:
Step-by-step explanation:
Step 1: From the given equation, taking the Left Hand Side (LHS) of the equation
Step 2: Simplify the LHS to make it equal to the Right Hand Side (RHS)
LHS = sin^4x - cos^4x = (sin²x)² - (cos²x)²
= (sin²x - cos²x)(sin²x + cos²x)
= sin²x - (1 - sin²x) since sin²x + cos²x = 1
= 2 sin²x - 1
= RHS
Hence proved.
You might be interested in
10+10 because the sum of their squares is 200, if you choose any other pair, the sum of their squares will be higher.
Answer:
i think y=3/4x-4.2
Step-by-step explanation:
Answer:
you wrote the answer
Step-by-step explanation:
I hope this helps you
x=42.8+6.9
x=49.7
a2+b2=25
or, (a+b)^2-2ab=25
or, (7)^2-2ab=25 [a+b=7]
or, 49-25=2ab
or, 24/2=an
•°• ab=12....